The Influence of Talent Management, Knowledge Management, and Employee Engagement on Employee Performance (Study in the HR Operations Section of PT. Perkebunan Nusantara III Medan) - Siti Salma Husnul Khatimah; Feronica Simanjorang (PT FORMOSA CENDEKIA GLOBAL, 2023)
Human resource management has progressed significantly over the years, and now largely addresses strategic tasks rather than administrative tasks. Human resources are one of the organization's strategic activities. The purpose of this research is to see the influence of Employee Engagement, Talent Management, and Knowledge Management on Job Performance at PT. Perkebunan Nusantara III (Persero) Medan HR Operational Section. In quantitative research methodology, an associative approach is used in this research. The research sample consisted of 45 respondents from PT. Perkebunan Nusantara III (Persero) Medan HR Operational Section. Employee performance is influenced simultaneously by the characteristics of talent management, knowledge management, and employee involvement by 76.2%, while the remaining 23.8% is influenced by variables not covered in the research.